Reservoirs of Porcine Circoviruses: A Mini Review - Zhai, Shao-Lun; Lu, Shou-Sheng; Wei, Wen-Kang; Lv, Dian-Hong; Wen, Xiao-Hui; Zhai, Qi; Chen, Qin-Ling; Sun, Yan-Wei; Xi, Yun (Frontiers in Veterinary Science, 2019)
Porcine circovirus (PCV) is one of the smallest known DNA viruses in mammals. At present, PCVs are divided into three species, PCV1, PCV2, and PCV3. PCV1 and PCV2 were found in the 1970s and the 1990s, respectively, whereas PCV3 was discovered recently in 2016. PCV1 does not cause diseases in pigs. However, PCV3, similar to PCV2, is reported to be associated with several swine diseases, including porcine dermatitis and nephropathy syndrome (PDNS) and reproductive failure. PCVs are very common in domestic pigs as well as wild boars. However, PCVs have been occasionally isolated from non-porcine animals, including ruminants (such as cattle, goats, wild chamois, and roe deers), rodents (such as NMRI mice, BALB/c mice, Black C57 mice, ICR mice, Mus musculus, and Rattus rattus), canines (such as dogs, minks, foxes, and raccoon dogs), insects (such as flies, mosquitoes, and ticks), and shellfish. Moreover, PCVs are frequently reported in biological products, including human vaccines, animal vaccines, porcine-derived commercial pepsin products, and many cell lines. PCVs are also abundant in the environment, including water samples and air samples. Interestingly, PCV1 and/or PCV2 antibody or antigen has also been detected in sera, stool samples and respiratory swab samples of human, revealing zoonotic potential of PCVs. Thus, PCVs inhabit many types of reservoirs. In this review, we summarize the reservoirs of PCVs, and this information would be helpful in understanding the natural circulating status and possible cross-species transmission of PCVs.